Examining Educational Administrators' Responses to Whistleblowing Cases in Schools in Türkiye - Demirel Yazıcı, Süheyla; Cemaloğlu, Necati (Technium Social Sciences Journal, 2025)
This study examines the procedures and practices implemented by educational administrators in provincial and district national education directorates in response to whistleblowing cases reported by schools in Türkiye. Employing a qualitative research design based on a phenomenological approach, data were collected through semi-structured interviews with 34 educational administrators selected using snowball sampling. The data were analyzed using descriptive and content analysis techniques with the support of MAXQDA 2020 software. The findings reveal that educational administrators evaluate whistleblowing cases through a multidimensional lens, considering the context of the incident, its specific elements, and relevant legal frameworks. It was determined that educational administrators collaborates with school administrations, internal departments, and other public institutions to develop effective solutions. The results suggest that most reported issues are perceived to stem from communication breakdowns; therefore, efforts are made to foster constructive dialogue between parties, with special attention paid to confidentiality. Depending on the nature of the issue, formal and legal processes are carried out by appointing investigators or inspectors. Additionally, psychosocial support is provided to students and staff, and protective measures- such as reassignment- are implemented when necessary. The study concludes that educational administrators exhibit a sensitive, proactive, and responsible attitude toward ethical and legal challenges, adopting a systematic, multi-actor, and solution-oriented approach in whistleblowing.